Assessing the Knowledge and Experience of Healthcare Workers in Zoonoses and the One Health Approach: A Cross-Sectional Study in Ghana - Godwin Dogbey; Brigid Unim; Abbiw Richard Kwamena; Godwin Clinton Ahiabor; Marta A. Kisiel; Xingwu Zhou; Apollo O. Maima; Amidu Abdul-Aziz; Ben Enyetornye; Robert Niayele; Anthony Amison Agbolosu; Kweku Asare-Dompreh (Environmental Health Insights)
Background: Healthcare workers’ (HCWs’) knowledge in delivering medical services is significantly influenced by their understanding of zoonotic diseases and the One Health (OH) concept. This study investigates the extent of HCWs’ knowledge and experience regarding zoonosis and the One Health approach in Ghana. Methods: This cross-sectional study involved 182 HCWs at the Tamale Teaching Hospital who completed questionnaires. Logistic regression was conducted to assess associations between socio-demographic factors and knowledge of zoonoses and OH. The correlation between knowledge and self-reported experience with zoonoses was assessed using Spearman’s correlation. Results: While 79.7% of HCWs correctly defined zoonoses, only 18.7% could sufficiently identify zoonotic diseases, and 59.3% were familiar with OH. The most commonly identified zoonotic disease was Ebola (75.3%), while brucellosis (12.1%) was the least recognized. Medical doctors were more likely to report previous encounters with zoonoses. Compared to medical doctors (reference HCWs), knowledge of OH was significantly higher among biomedical scientists (OR = 2.25, 95% CI: 0.72-7.37) and lower among nurses (OR = 0.92, 95% CI: 0.33-2.60). Professional experience of more than 5 years was associated with greater knowledge of rabies and tuberculosis. There was no significant correlation between knowledge of zoonoses and self-reported experience with any of the assessed diseases, except for a weak negative correlation with trypanosomiasis (Spearman’s r  = –0.206, P  = .005). Conclusions: The majority of HCWs have inadequate knowledge of zoonosis. Although most HCWs are aware of OH, they have limited experience with zoonosis and OH. Curricula for training HCWs should include more courses on zoonosis and arrange refresher training programs for HCWs. Enhancing HCWs’ expertise in zoonotic disease surveillance and detection is crucial for early identification and control of zoonoses, aiding in the prevention of future outbreaks.